Dataset of traffic dynamics during the 2020 Glass Wildfire Evacuation - Rohaert, Arthur; Janfeshanaraghi, Nima; Kuligowski, Erica D.; Ronchi, Enrico (Lund University, 2023)
This dataset contains the

This dataset has been sourced from the Performance Measurement System of the California Department of Transportation. The data has been processed, analysed, presented and summarized in the paper: Rohaert et al., ‘The analysis of traffic data of wildfire evacuation: the case study of the 2020 Glass Fire’, [Submitted for peer-review to an international journal.], 2023.

Acknowledgements

This work has been funded under award 60NANB21D118 from the National Institute of Standards and Technology (NIST), U.S. Department of Commerce.
Keywords: Glass Fire; evacuation; traffic dynamics; wildfire; wildland-urban interface; Civil Engineering; Samhällsbyggnadsteknik